Maqashid Sharia and Penal Mediation in Achieving the SDGs: A Study of Domestic Violence - Dudung Abdul Razak; Faisal Efendi; Afrikal Candra; Lili Suarni; Musa Zulkifli; Nurlaila Nurlaila (Profetika: Jurnal Studi Islam, 2026)
Objective: Domestic violence is a complex issue involving various social, legal, moral aspects and sdgs. Therefore, its handling requires a comprehensive approach based on the principles of justice and humanity. This issue not only threatens family harmony but also contradicts the principles of public interest in Islamic law. Theoretical framework: From the perspective of Maqashid Sharia, the protection of domestic violence victims has a strong foundation, namely the preservation of life (hifz an-nafs), honor (hifz al-'irdh), and lineage (hifz an-nasl), which are the main objectives of Islamic law. Literature review: Domestic violence is increasingly common in today's society. The increasing number of cases in court, lack of understanding, and the numerous channels available make victims reluctant to file a complaint. Methods: This study uses the library research method with a normative approach through literature study to analyze the relationship between Maqashid Sharia and penal mediation in the context of domestic violence.  Results: The settlement of domestic violence cases is carried out through criminal procedural law, in accordance with Law Number 8 of 1981 concerning Criminal Procedure Law, as well as other related laws, such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law). In this case, the settlement efforts made by the Court are in line with the objectives of Sharia, namely to provide protection for the five main principles in Islam, namely: preserving religion, life, reason, lineage, and property. The concept of penal mediation can be an alternative in resolving domestic violence cases, as it is based on restorative justice, which aims to provide justice by creating a balance between the victim and the perpetrator, as well as finding a win-win solution. Penal mediation is also expected to be a solution to various problems in the Indonesian criminal justice system. Implications: The implication of this study is the need to increase education and socialization regarding the PKDRT Law for the community and related agencies, so that women will be more courageous in reporting acts of violence they experience. The public is expected to play an active role in addressing and preventing domestic violence. Novelty: The novelty of this article examines how penal mediation and Maqashid Sharia are applied in domestic violence cases. It lies in the path taken by the husband and wife in this case. The Sustainable Development Goals (SDGs) the resolution of domestic violence cases in Indonesia can be seen as part of efforts to achieve several relevant goals, including SDGs 5 (Gender Equality) and SDGs 16 (Peace, Justice, and Strong Institutions).